Transcriptome analysis reveals the molecular mechanisms of response to an emergent yellow-flower disease in green Chinese prickly ash (Zanthoxylum schinifolium) - Fan Xu (Nature Portfolio, 2021)
Abstract Chinese prickly ash (Zanthoxylum) is extensively used as spice and traditional medicine in eastern Asian countries. Recently, an emergent yellow-flower disease (YFD) break out in green Chinese prickly ash (Zanthoxylum schinifolium, Qinghuajiao in Chinese) at Chongqing municipality, and then leads to a sharp reduction in the yield of Qinghuajiao, and thus results in great economic losses for farmers. To address the molecular response for the emergent YFD of Qinghuajiao, we analyzed the transcriptome of 12 samples including the leaves and inflorescences of asymptomatic and symptomatic plants from three different towns at Chongqing by high-throughput RNA-Seq technique. A total of 126,550 genes and 229,643 transcripts were obtained, and 21,054 unigenes were expressed in all 12 samples. There were 56 and 164 different expressed genes (DEGs) for the AL_vs_SL (asymptomatic leaf vs symptomatic leaf) and AF_vs_SF (asymptomatic flower vs symptomatic flower) groups, respectively. The results of KEGG analysis showed that the “phenylpropanoid biosynthesis” pathway that related to plant–pathogen interaction were found in AL_vs_SL and AF_vs_SF groups, and the “Plant–pathogen interaction” found in AF_vs_SF group, implying that this Qinghuajiao YFD might cause by plant pathogen. Interestingly, we detected 33 common unigenes for the 2 groups, and almost these unigenes were up-regulated in the symptomatic plants. Moreover, most of which were homologs to virus RNA, the components of viruses, implying that this YFD was related to virus. Our results provided a primary molecular basis for the prevention and treatment of YFD of Qinghuajiao trees.